Mapping neurological symptoms and muscle tension representations in impaired gray matter volume of Wilson disease - Yufeng Ding; Kegang Cao; Wenming Yang; Sheng Hu; Jing Zhang; Yulong Yang; Xuran Zhang (Frontiers in Neurology)
ObjectivesNeurodegenerative changes are key manifestations of Wilson disease (WD), causing neurological symptoms including parkinsonism, tremors, and dystonia. However, the neuroimaging correlates of specific neurological manifestations (especially dystonia) in WD remain poorly characterized.Methods37 WD patients and 37 healthy controls (HC) were recruited. All subjects underwent structural magnetic resonance scanning, muscle biomechanical measurements, and the Unified Wilson Disease Rating Scale for Neurology (UWDRS-N) assessment. Neurodegenerative changes, identified as gray matter volume (GV) changes, were analyzed via voxel-based morphometry (VBM) in WD compared to HC. Clinical symptoms were linked to GV changes in WD patients’ brains.ResultsCompared with HC, WD patients had GV loss in the bilateral caudate nucleus, putamen, cerebellum (Crus1), left amygdala, right posterior insular lobe, and right parahippocampal gyrus and increased GV in the bilateral anterior insular lobes. In cortical areas, UWDRS-N significantly negatively correlated with GV in the bilateral posterior insula lobes, part of temporal lobe, optic cortex, frontal lobe, and cingulate cortex, while positively correlated with that in bilateral anterior insular lobes and putamen. Moreover, the GV from the left parahippocampal gyrus, bilateral hippocampus, and bilateral caudate nucleus showed a strong positive correlation with the F value of the right gastrocnemius medial head.ConclusionIn WD patients with neurological symptoms, obvious abnormal GV values in the cortico-striatal-thalamo-cortical (CSTC) circuit were noted. These GV changes were linked to UWDRS-N and correlated with muscle tension. The study mapped UWDRS-N and muscle biomechanics in GV-impaired areas, suggesting altered GV (especially in basal ganglia) as a key imaging sign of WD severity. This indicates that the CSTC circuit could act as a biomarker for WD neurological symptoms and affect WD dystonia mechanisms. Additionally, it shows that muscle-related biological parameters can assess WD dystonia severity and neurological damage.Clinical trial registrationclinicaltrials.gov, identifier NCT05305872.